Pyro‐Phototronic Effect Induced Circularly Polarized Light Detection with a Broadband Response - Qianwen Guan; Zeng‐Kui Zhu; Huang Ye; Chengshu Zhang; Hang Li; Chengmin Ji; Xitao Liu; Junhua Luo (Advanced Science)
Abstract Photopyroelectric‐based circularly polarized light (CPL) detection, coupling the pyro‐phototronic effect and chiroptical phenomena, has provided a promising platform for high‐performance CPL detectors. However, as a novel detection strategy, photopyroelectric‐based CPL detection is currently restricted by the short‐wave optical response, underscoring the urgent need to extend its response range. Herein, visible‐to‐near‐infrared CPL detection induced by the pyro‐phototronic effect is first realized in chiral‐polar perovskites. Specifically, chiral‐polar multilayered perovskites (S‐BPEA)2FAPb2I7 (1‐S, S‐BPEA = (S)‐1‐4‐Bromophenylethylammonium, FA = formamidinium) with spontaneous polarization shows intrinsic pyroelectric and photopyroelectric performance. Strikingly, combining its merits of the pyro‐phototronic effect and intrinsic wide‐spectrum spin‐selective effect, chiral multilayered 1‐S presents efficient photopyroelectric‐based broadband CPL detection performance spanning 405–785 nm. This research first realizes photopyroelectric‐based infrared CPL detection and also sheds light on developing high‐performance broadband CPL detectors based on the pyro‐phototronic effect in the fields of optics, optoelectronics, and spintronics.